Case report: Single-session double-Ilizarov lengthening technique in the treatment of a child with congenital fibular deficiency - Wen Shu; Changjie Yue; Haobo Zhong; Xin Tang (Frontiers Media S.A., 2022)
BackgroundCongenital fibular deficiency is a rare disease with a broad spectrum of deformities. Associated anomalies complicate the symptoms of patients and, consequently, individualized treatments that aim at normal function and acceptable appearance.Case presentationWe present a case of congenital femoral and fibular shortening in the right lower limb with foot anomaly at school age. The patient underwent limb lengthening procedure in a single session on the right femur and tibia at the same time using a double-Ilizarov frame. The functional and cosmetic of his right lower extremity achieved a good outcome. Complications were minimal except for the superficial infection. Treatment lasted for 9.2 months, allowing for returning the patient to functional activity as soon as possible.ConclusionA satisfactory result was obtained with limb lengthening in a single session using double Ilizarov external fixators in a school-aged patient with congenital fibular deficiency.